Effect of Chlorhexidine Gluconate (0.2%), Combination (0.2% Chlorhexidine and 0.05% Sodium Fluoride), and Green Tea Extract (0.5%) Mouth Rinses on Colony Count Changes of Streptococcus mutans and Lactobacillus in Saliva - A Randomized Controlled Trial - B. S. Suma; Kumari Sony; Nirmala Kumari; S. N. Pandey (Wolters Kluwer Medknow Publications, 2024)
Introduction Streptococcus mutans and Lactobacillus acidophilus are the well-known etiological factors for dental caries. Chlorhexidine (CHX) gluconate is the "gold-standard" antimicrobial agent but having adverse effects such as brown staining of the teeth and altered taste. Thus, there is a need for an alternative herbal product. Objective This study was done to compare the efficacy of CHX gluconate (0.2%) and combination (0.2% CHX and 0.05% sodium fluoride [NaF]) mouth rinses to that of green tea extract (0.5%) mouth rinse in reducing the salivary count of S. mutans and L. acidophilus in dental students. Materials and Methods The sample size of the study was 75 dental students with ≥4 decayed, missing, and filled teeth (DMFT) index. They were divided into three equal groups to test various mouth rinses against S. mutans and Lactobacillus. Unstimulated salivary samples were collected at baseline and postrinse (14 days) and tested for the colony-forming units of S. mutans and Lactobacillus. The Chi-square test was used to ascertain the demographic characteristics of the study population. One-way ANOVA statistics and paired t-test were applied to calculate the inferential statistics between the variables. The statistical constant was fixed at P < 0.05. Results The results of the study indicated that there was a statistically significant reduction in S. mutans and Lactobacilli count in all the three study groups. Conclusion Green tea mouth rinse can be a promising preventive therapy worldwide for the prevention of dental caries but CHX mouthwashes are superior in reduction of S. mutans and Lactobacillus.